THE IMPACT OF DIGITAL 3D SCANNING AND VIRTUAL FITTING TECHNOLOGIES ON GARMENT FIT ACCURACY AND PROCESS OPTIMIZATION IN THE FASHION INDUSTRY (American Journal of Research in Humanities and Social Sciences, 2026)
This article examines the impact of digital 3D body scanning and virtual fitting technologies on garment fit accuracy and process optimization in the fashion industry. It examines the potential of 3D scanning for creating digital body models and integrating them into clothing design, as well as the role of virtual fitting rooms in improving fit accuracy, personalization, reducing returns, and optimizing production processes. The advantages and limitations of these technologies are analyzed, including issues of fabric simulation fidelity, data standardization, and the privacy of personal measurements. The findings demonstrate that 3D technologies have the potential to significantly improve the efficiency and sustainability of the fashion industry, providing new opportunities for customization and digitalization of processes.